Investigation of clinical characteristics and genome associations in the 'UK Lipoedema' cohort. - Dionysios Grigoriadis; Ege Sackey; Katie Riches; Malou van Zanten; Glen Brice; Ruth England; Mike Mills; Sara E Dobbins; Li Ling Lee; Lipoedema Consortium; Genomics England Research Consortium; Steve Jeffery; et al. (PLoS ONE)
Lipoedema is a chronic adipose tissue disorder mainly affecting women, causing excess subcutaneous fat deposition on the lower limbs with pain and tenderness. There is often a family history of lipoedema, suggesting a genetic origin, but the contribution of genetics is currently unclear. A tightly phenotyped cohort of 200 lipoedema patients was recruited from two UK specialist clinics. Objective clinical characteristics and measures of quality of life data were obtained. In an attempt to understand the genetic architecture of the disease better, genome-wide single nucleotide polymorphism (SNP) genotype data were obtained, and a genome wide association study (GWAS) was performed on 130 of the recruits. The analysis revealed genetic loci suggestively associated with the lipoedema phenotype, with further support provided by an independent cohort taken from the 100,000 Genomes Project. The top SNP rs1409440 (ORmeta ≈ 2.01, Pmeta ≈ 4 x 10-6) is located upstream of LHFPL6, which is thought to be involved with lipoma formation. Exactly how this relates to lipoedema is not yet understood. This first GWAS of a UK lipoedema cohort has identified genetic regions of suggestive association with the disease. Further replication of these findings in different populations is warranted.